Does Anxiety Attachment Determine Sexting? A Meta-Analysis - Rahardjo, Wahyu; Andayani, Tri Rejeki (Faculty of Psychology Universitas Gadjah Mada, 2024)
Sexting is sexual behavior related to the use of communication technology. Anxiety attachment is a determining factor because it influences emotion-based social relations regarding sexuality. Therefore, a meta-analysis needs to be conducted to confirm this. The aim of this study was to measure the strength of the correlation between anxiety attachment and sexting by considering the effect size. This meta-analysis involved 36 studies with a total of 17,568 participants. The findings showed a weak correlation between anxious attachment and sexting (r = 0.113; z = 4.816, p < .01; 95% CI [0.06; 0.17]). This same correlation pattern was observed when the assessment was conducted among the general and married people group (r = 0.125; z = 2.757, p < .01; 95% CI [0.04; 0.21]), and the high school and college student group based on their educational level (r = 0.107; z = 4.086, p < .01; 95% CI [0.06; 0.16]). For these three groups, the heterogeneity test showed significant results, indicating a symmetrical distribution of scores based on the results of the funnel test and Egger’s test. The findings also showed no publication bias. In other words, this meta-analysis proves that anxiety attachment is a determining factor but not a strong antecedent of sexting.